Morphological and Molecular Identification, Virulence, Host Range, and Cultural Requirements of Diaporthe vexans Associated with Eggplant Fruit Rot - Salma Firyal Khairunnisa; Tri Asmira Damayanti; Hagia Sophia Khairani (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2026)
Diaporthe vexans (syn: Phomopsis vexans) is a major postharvest pathogen causing Phomopsis blight and fruit rot in eggplant (Solanum melongena), leading to significant economic losses in Indonesia. This study aimed to identify the causal agent of eggplant fruit rot, evaluate its virulence and host range among some Solanaceous crops, and determine the optimal synthetic media for mycelial growth and sporulation. Fungal isolates were obtained from symptomatic eggplants at Kemang Wholesale Market, Bogor, and identified through morphological and molecular analysis amplifying the ITS region. Virulence was tested using mycelial plug and conidial suspension methods, while host range assays were conducted on tomato, chili, black nightshade, and cucumber. Isolate V2 was identified as putatively belonging to D. vexans, showing 98% sequence identity with D. vexans from the Philippines and submitted to the GenBank with accession number PV936605.1. Pathogenicity tests indicated that the apical and middle regions of eggplant fruits tended to be more susceptible to infection than the basal region. Host range evaluations revealed that while D. vexans is primarily asssociated with eggplant but was capable of infecting other Solananeous hosts under artificial inoculation. For laboratory assays, potato dextrose agar (PDA) supported the highest radial growth (79.03 mm), but cornmeal agar (CMA) was the effective for stimulating dense sporulation (4.9 x 106 spores mL⁻¹). These results indicate that D. vexans poses a cross-contamination risk during postharvest storage and that among the media evaluated, CMA was the most effective medium for inoculum production of isolate V2. Keywords: cornmeal agar, ITS region, pathogenicity, postharvest pathogen, Solanum melongena